Posted by **kathy** on Thursday, February 26, 2009 at 10:05pm.

1. (x+1)(x+1)=x^2+x+x+1=x^2+2x+1

11*11=121

2. (x+1)(x+2)=x^2+2x+x+2=x^2+3x+3

11*12=132

3. (x+1)(x+3)=x^2+3x+x+3=x^2+4x+3

11*13=143

What are the similarities between the two answers in each pair of products?

## Answer This Question

## Related Questions

- Math - Which ratios does NOT form a proportion? 1. 24/96 , 27/108 2. 17/102 , 12...
- MATH HELP - 1. Which ratios form a proportion? Use equivalent ratios to test ...
- Chemistry(Please check answers) - 1) The standard molar entropy value of N2 (g) ...
- Calculus - This is a large problem, sorry for the trouble. if f(x) = sqrt(x^3 + ...
- Math - Suppose M is between L and N. Use the Segment Addition Postulate to solve...
- CHECK!!!+ math - hi here is my question: what is the general term of the ...
- Psychology - identify the major similarities and differences that exists ...
- Chemistry - O3 + NO --> O2 + NO2 (all in gas state) Calculate the change in ...
- psychology - I would like the entire class to identify the major similarities ...
- Science/physics - Two vectors A and B have magnitude A = 3.00 and B = 3.00. ...

More Related Questions